The role of congruence in policy priorities between citizens and elites in citizens' political attitudes and behaviour - Reher, S (2014)
This thesis shows that citizens whose policy concerns are higher on political elites' agendas are more likely to be satisfied with democracy and to vote in elections. It develops a theoretical framework to explain the influence of the previously neglected variable priority congruence on democratic satisfaction and turnout and provides empirical evidence for it. The thesis thereby makes significant contributions to our knowledge about the ingredients of democratic legitimacy. Previous research shows that political representation, as measured by proximity between citizens' and elites' policy positions, is linked to democratic satisfaction. In this thesis, it is argued that congruence in priorities has a similar effect because citizens are likely to perceive elites who emphasise their concerns as responsive to societal needs and public opinion. The empirical analyses suggest that democratic satisfaction is indeed influenced by priority congruence, yet less so amongst more politically sophisticated individuals as well as in younger democracies and countries with lower levels of democracy and governance. These differences are probably due to variation in citizens' expectations towards elite behaviour and the democratic system. Elite attention to citizens' concerns moreover influences their decision to turn out in elections. If voters' issue priorities are salient in the campaign, they are likely to perceive the election to be more important. Moreover, they will find it easier to evaluate parties and make their vote choice. These mechanisms are shown to be less relevant amongst partisans, since party attachment mobilises voters and facilitates their vote choice. Again, previous policy-based explanations of turnout focus on positions, largely ignoring priorities. The hypotheses are tested through statistical analysis of data from voter and candidate surveys as well as media content analyses. The data come from all 27 European Union countries in 2009, whereby several hypotheses are only tested in Germany due to data availability.